Neuronatin promotes SERCA uncoupling and its expression is altered in skeletal muscles of high‐fat diet‐fed mice. Issue 22 (5th November 2021) - Braun, Jessica L.; Teng, Allen C. T.; Geromella, Mia S.; Ryan, Chantal R.; Fenech, Rachel K.; MacPherson, Rebecca E. K.; Gramolini, Anthony O.; Fajardo, Val A.
Abstract : Neuronatin (NNAT) is a transmembrane protein in the endoplasmic reticulum involved in metabolic regulation. It shares sequence homology with sarcolipin (SLN), which negatively regulates the sarco(endo)plasmic reticulum Ca 2+ ‐ATPase (SERCA) that maintains energy homeostasis in muscles. Here, we examined whether NNAT could uncouple the Ca 2+ transport activity of SERCA from ATP hydrolysis, similarly to SLN. NNAT significantly reduced Ca 2+ uptake without altering SERCA activity, ultimately lowering the apparent coupling ratio of SERCA. This effect of NNAT was reversed by the adenylyl cyclase activator forskolin. Furthermore, soleus muscles from high fat diet (HFD)‐fed mice showed a significant downregulation in NNAT content compared with chow‐fed mice, whereas an upregulation in NNAT content was observed in fast‐twitch muscles from HFD‐ versus chow‐ fed mice. Therefore, NNAT is a SERCA uncoupler in cells and may function in adaptive thermogenesis. Abstract : Neuronatin reduces sarco(endo)plasmic reticulum Ca 2+ ‐ATPase (SERCA)‐mediated calcium uptake without altering SERCA activity, thereby uncoupling calcium transport from ATP hydrolysis. In C57BL/6 mice, 12 weeks of high fat feeding leads to a reduction in neuronatin content in the soleus but an upregulation in neuronatin content in fast muscle types including the extensor digitorum longus and red and white gastrocnemius.